Antiplatelet activity of deferiprone through cyclooxygenase-1 inhibition. (18th May 2020) - Tran, Ngan Thi; Akkawat, Benjaporn; Morales, Noppawan Phumala; Rojnuckarin, Ponlapat; Luechapudiporn, Rataya
Abstract: Thalassemia patients are susceptible to both iron overload and thromboembolism. Deferiprone is an iron chelator that shows an antiplatelet activity and thus may alleviate platelet hyperactivation in thalassemia. Therefore, this study aimed to characterize the inhibitory effects and mechanisms of deferiprone on normal human platelets. The results illustrated that deferiprone inhibited platelet aggregation at the iron chelating concentrations (0.08–0.25 mmol/l). Deferiprone inhibited human platelet aggregation stimulated by arachidonic acid and ADP more potently than epinephrine and collagen, with the IC50 of 0.24 mmol/l and 0.25 mmol/l vs . 3.36 mmol/l and 3.73 mmol/l, respectively. Interestingly, deferiprone significantly inhibited COX-1 activity, with the IC50 of 0.33 mmol/l, and slightly increased cAMP level at the high concentration of 4 mmol/l. Moreover, the results from molecular docking showed that deferiprone interacted closely with key residues in the peroxidase active site of COX-1. These results suggested that deferiprone possessed antiplatelet activity mainly through the inhibition of COX-1 activity.